Pelatihan Pembuatan Jelly Drink Bergizi Terfortifikasi Bayam Hijau dan Bayam Merah untuk Anak - Tri Sunarsih; Endah Puji Astuti; Edhy Tri Cahyono; Pramitha Sari; Elvika Fit Ari Shanti (Universitas Jenderal Achmad Yani Yogyakarta, 2025)
Background: Nutritional problems in children, particularly stunting, anemia, and malnutrition, remain a serious challenge in Indonesia. Children's low interest in consuming vegetables and limited family skills in processing local foods are factors that exacerbate this condition. One innovative solution is the development of Supplementary Feeding (PMT) products based on nutritious, attractive, and affordable local foods, such as jelly drinks fortified with green spinach and red spinach. Methods: This community service activity was carried out through skills-based training with a participatory-applicative approach. The methods used included interactive lectures, demonstrations, direct practice, group discussions, and evaluation with pre-tests, post-tests, and skills observations. The training participants were 30 Posyandu cadres in Demangrejo Village, Sentolo Subdistrict, Kulon Progo, who were selected because they have a strategic role in nutrition education and stunting prevention programs. Results: The results of the activity showed a significant increase in the knowledge and skills of the participants. The average knowledge score increased by 46.7% after the training, particularly regarding the nutritional benefits of green spinach, red spinach, and moringa leaves, processing techniques, and principles of maintaining nutritional content during cooking. All participants successfully made their own fortified jelly drink, producing a product with a natural bright color, soft sweetness, and a chewy texture, and received positive assessments in organoleptic tests. Furthermore, most participants expressed interest in applying these skills at home, both for family consumption and as a small business opportunity. Conclusion: This training effectively increased the capacity of integrated health post (Posyandu) cadres in utilizing local foods for innovative PMT (Food and Nutritional Supplements). The impact not only increased nutritional knowledge and skills but also has the potential to strengthen family food security and open up opportunities for community economic empowerment. This activity can be replicated in other regions by adapting to the potential of local food sources.